Adopting mobile money - Batista, Cátia (2020)
Who uses mobile money, and what do people do with it? This paper describes mobile money adoption patterns following the experimental introduction of mobile money for the first time in rural areas of Southern Mozambique. We use administrative and household survey data to characterize adopters as well as their mobile money usage patterns over three years. Adopters of mobile money (and early adopters in particular) are more educated than nonadopters, and they are also more likely to already hold a bank account. Positive self-selection of adopters should be considered when introducing mobile money as a tool for rapid financial inclusion.